تأثير الخرائط الذهنية لترقية مهارة الكتابة لدى طلبة في مدرسة بحر العلوم المتوسطة الاسلامية سنجنجي - Nur Hayati (Lembaga Yasin AlSys, 2026)
Although the use of visual strategies in learning, such as mind mapping, has received increasing attention in previous studies, research that specifically addresses its effect on improving Arabic writing skills among students in Islamic junior high schools remains limited. This study aims to analyze the effect of using mind mapping on improving the writing skills of students at Bahrul Ulum Islamiyah Sengganji Islamic Junior High School. The researcher employed a quantitative method with a quasi-experimental design using a nonequivalent two-group model, involving 60 students selected through purposive sampling. The data were collected using pretests and posttests, observation, and documentation, and were then analyzed using an independent-samples t-test with SPSS 26.0. The results showed a statistically significant difference between the experimental and control groups (t = -5.335, p < 0.05), indicating that the use of mind mapping effectively contributed to improving students’ ability to organize ideas, enhance memory and concentration, and produce coherent and well-organized texts. These results contribute to the development of Tony Buzan’s cognitive theory of mind mapping, while also broadening understanding of effective strategies for teaching productive skills in Arabic. The study concludes that mind mapping plays a vital role in facilitating organized and creative writing in Arabic language learning, and recommends its integration into educational practices to encourage active and purposeful learning. The implications of this study include theoretical contributions to the field of Arabic language teaching, as well as practical recommendations for educational institutions seeking to improve students’ proficiency in writing skills. This study also opens avenues for future research on integrating mind mapping into the development of other language skills, such as reading and reading comprehension.